2021
DOI: 10.1111/jgh.15579
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic powder TC‐325 treatment of malignancy‐related upper gastrointestinal bleeds: International registry outcomes

Abstract: Background and Aim Upper gastrointestinal tumors account for 5% of upper gastrointestinal bleeds. These patients are challenging to treat due to the diffuse nature of the neoplastic bleeding lesions, high rebleeding rates, and significant transfusion requirements. TC‐325 (Cook Medical, North Carolina, USA) is a hemostatic powder for gastrointestinal bleeding. The aim of this study was to examine the outcomes of upper gastrointestinal bleeds secondary to tumors treated with Hemospray therapy. Methods Data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 18 publications
0
15
0
1
Order By: Relevance
“…As many have reported 22 25 , 28 , 30 , 31 , 39 , the noncontact powder application system is easy to use, and little experience or technical expertise is needed. From our experience, only 15–20 min of training is required before the first use of PEO.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As many have reported 22 25 , 28 , 30 , 31 , 39 , the noncontact powder application system is easy to use, and little experience or technical expertise is needed. From our experience, only 15–20 min of training is required before the first use of PEO.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, its role in treating gastrointestinal bleeding has been proven valid 22 , 27 – 29 , especially when bleeding sites were located in difficult anatomical positions that conventional instruments could not reach 25 , 28 . Many studies have emphasized the short-term efficacy of haemostatic powder 23 , 25 , 27 , 28 , 31 ; in some cases with massive haemorrhage, haemostatic powder was efficacious as a bridge to surgery. Moreover, a newly published study, which enrolled patients with large lesions and antithrombotic users, demonstrated that EndoClot polysaccharide haemostatic powder (PHP) had a tendency to decrease delayed bleeding in the early postoperative phase in high-risk patients 30 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our case, endoscopic therapy was not pursued as the patient was hemodynamically stable with appropriate incrementation in hemoglobin levels following blood transfusion. If the patient had decompensated, we would have considered hemostatic powder application due to its high success rate in achieving initial hemostasis, although 30-day rebleeding rates remain as high as 15% [ 16 - 19 ]. There is also a risk of hemostatic powder spray obstructing the target lesion if rebleeding occurs, thereby making other endoscopic therapies difficult [ 13 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…[13]). Der Autor sieht einen Hauptnutzen vor allem in der Anwendung ▪ bei der diffusen Tumorblutung, da hier ein breitflächiges Nichtkontaktverfahren vorteilhaft ist [14], sowie ▪ bei aufgrund der Lokalisation (und ggf. auch der Untersucherexpertise) schlecht einseh-und einstellbarer Blutung (z.…”
Section: Sondersituation Bei Covid-19unclassified